Case Report: A complex congenital bilateral multidirectional glenohumeral hyperlaxity with instability: surgical, anatomical, and forensic insights - Capuzzo, Marco; Mizuno, Fernando Henrique; Maci, Gaetano; Carboni, Luca; Emmi, Aron; Macchi, Veronica; De Caro, Raffaele; Porzionato, Andrea; Boscolo-Berto, Rafael (Frontiers in Surgery, 2025)
Multidirectional instability (MDI) of the shoulder joint involves the looseness of the joint capsule in multiple directions, resulting in difficulties in keeping the head of the humerus centered within the glenoid fossa. There is still considerable debate about the optimal treatment approach, ranging from conservative management to surgical intervention and it is even more challenging for complex or bilateral cases. An 18-year-old male with a rare congenital bilateral multidirectional glenohumeral hyperlaxity and instability is reported. After excluding other medical conditions, the patient was diagnosed with benign joint hypermobility syndrome. Despite undergoing four months of conservative treatment with physical therapy, there was no significant improvement, leading to the decision for bilateral surgical intervention. The procedure combined an autograft Posterior Bone Block procedure with the Arthroscopic Subscapularis Augmentation (ASA) Technique to enhance anterior stability. The latter involved a tenodesis of the superior third part of the subscapularis tendon. The fixating hole was drilled at the top position of the glenoid edge, and the insertion on the subscapularis tendon was positioned inferiorly to the superior border of the tendon. After surgery, an accelerated post-operative rehabilitation protocol for each shoulder was implemented. At the one-year follow-up after the second surgery, the patient demonstrated substantial improvements in shoulder stability and functional outcomes. The Constant Shoulder Score (CSS) improved from 53 to 77 for both shoulders, indicating a 45.3% improvement and progression from “Moderate” to “Good” function. Similarly, the American Shoulder and Elbow Surgeons (ASES) Orthopaedic Scores improved from 58.33 to 88.32 for the right shoulder (51.4% improvement) and from 61.65 to 94.99 for the left shoulder (54.1% improvement), reflecting a transition from “Fair” to “Good” and “Excellent” function, respectively. Importantly, no short- or medium-term adverse events were reported, and the patient achieved a full return to normal activities. The combination of autograft Posterior Bone Block and ASA techniques has proven to be a successful option in this case for restoring function and stability, even in rare and complex cases of congenital bilateral multidirectional glenohumeral hyperlaxity and instability. Nonetheless, in these complex cases, critical surgical, anatomical, and forensic issues should be carefully considered.